2020
DOI: 10.2741/4796
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of cuticular genes during insect metamorphosis

Abstract: Introduction 3. Hormonal regulation of insect metamorphosis 3.1. Larval molting and pupal metamorphosis 3.2. Alterations of cells during metamorphosis 4. Transcriptional regulation of cuticle protein genes during metamorphosis 4.1. CP genes expressed pre-pupal stage showed six distinctive developmental patterns 4.2. Responsiveness of CPs to the ecdysone pulse in vitro is reflected in the developmental profile 4.3. Prepupal CP genes showed different ecdysone responsiveness, resulting in different developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…A plethora of physiological processes has been reported to be affected by the knockdown of cuticle protein, including locomotion, mechanical support, sensory perception, molting, and resistance response [ 44 ]. The molting process also involves a principal hormone in the insects, i.e., the juvenile hormone (JH) binding protein [ 47 ]. The transcriptome sequencing data indicated that in WBPH, there is a >6.0-fold upregulation of this hormone, clearly indicating that resistant hosts trigger changes in the developmental processes in these insects, specifically those related to molting and metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of physiological processes has been reported to be affected by the knockdown of cuticle protein, including locomotion, mechanical support, sensory perception, molting, and resistance response [ 44 ]. The molting process also involves a principal hormone in the insects, i.e., the juvenile hormone (JH) binding protein [ 47 ]. The transcriptome sequencing data indicated that in WBPH, there is a >6.0-fold upregulation of this hormone, clearly indicating that resistant hosts trigger changes in the developmental processes in these insects, specifically those related to molting and metamorphosis.…”
Section: Discussionmentioning
confidence: 99%